Educação infantil na escola do campo: o que as crianças no sinalizam sobre este contexto - Löffler, Daliana (2013)
This present paper shows the results of Master s Research on Kindergarten in the field school, what the children indicate in this context, liked to the Graduate Program in Education - Master of Education PPGE / UFSM Research s Line School Practices and Public Policies, and the "Research Group and Contemporary Studies in Education and Childhood." The research had as central theme of study the kindergarten in the context of the field school, in this context, the focus of analysis was in the jokes developed by children, specifically the starring game. The aim of the study was to know what children's jokes in the kindergarten in the field can signal us about the meanings that they build on this school. To this end, we conducted a qualitative research, ethnographic approach, taking as instrument of production the data, the records by images of the moments of gambling starring game. Guided the theoretical framework of Cultural Historical Theory (Leontiev, 1988, Vygotsky, 1988, 2009) and the Education of Children (Oliveira-Formosinho, 2008) this research contributes to the building of a quality work in kindergarten, highlighting the relevance of listening to the children in the organizational processes at school. As results, we can say that the kindergarten in the field, is signified by children as a space of socialization, but also a place to live a "not to be" given the excessive preoccupation with the preparation of the small kids to access to fundamental education and the adequacy the standards of urban life.